Dual Arm Free Flying Space Robot Trajectory Planning Using Polynomial. (26th February 2015) - Rathee, Rishikesh; Pathak, Pushparaj Mani
Abstract : The paper presents path planning of dual arm free flying space robot using smooth functions of time. Kinematic and dynamic modeling of dual arm free flying space robot is presented first. Using kinematic model, the Jacobian of the system has been derived, and using dynamic model, equations of motion are derived. A path planning methodology for planar system is developed using smooth function of time such as polynomials. Due to nonholonomic behaviour of the manipulator in the zero gravity environment linear and angular momentum is conserved. The proposed method yields input trajectories that drive both the manipulator and the base to a desired configuration. Joint torque curves can be obtained by introducing this joint trajectory curves in equation of motion of the space robot.